Experimental Arterial Thrombosis in Genetically or Diet Induced Hyperlipidemia in Rats - De Curtis, Amalia; D’Adamo, Maria Cristina; Amore, Concetta; Polishchuck, Roman; Di Castelnuovo, Augusto; Donati, Maria Benedetta; Iacoviello, Licia (Thrombosis and Haemostasis, 2001)
To investigate the relationship among lipids, coagulation and thrombosis in the absence of atherosclerosis, spontaneous or dietary-induced hyperlipidemic (FHL) rats were studied. FHL showed higher levels of coagulation factors VII, IX, X, VIII and XII and a shortening of the occlusion time (OT) of an artificial arterial prosthesis as compared with normolipidemic (FNL) animals. Damage of abdominal aorta of FHL was followed by increased fibrin deposition in the vascular intima as compared to FNL. After 5 months of cholesterol-rich diet FNL showed increased cholesterol, triglycerides and factor II, VII, IX, X, XII levels. A significant shortening of the OT and increased fibrin deposition was also observed. Two-month diet withdrawal restored the initial condition. Warfarin treatment, at a dose decreasing vitamin K-dependent factor to levels found in FNL, prolonged the OT and reduced fibrin deposition, without modifying F XII or changing lipid profile. An increase in the activated form of F VII was observed. In contrast, no difference was found in F VII clearance. High lipid levels favour the process of thrombus formation by increasing the activation of vitamin K-dependent coagulation factors. Low-dose warfarin treatment reverts the prothrombotic effect of hyper-lipidemia.
Keywords: Lipids; arterial thrombosis; coagulation factors; rats